Dentofacial features of obstructive sleep apnoea syndrome (OSAS) among army personnel based in Kelantan - Hashim, Hasnah (Pusat Pengajian Sains Pergigian, Universiti Sains Malaysia, 2006)
Obstructive sleep apnea (OSA) is repeated complete or partial upper airway obstruction during sleep, causing cessation of breathing (apnea) or reduction in airflow (hypopneas) despite persistent respiratory effort. It occurs in 9% and 24% middle-aged women and men respectively while obstructive sleep apnea syndrome, OSAS (OSA plus presence of symptoms such as excessive daytime sleepiness) occurs in 2% and 4% middle-aged women and men respectively. The objectives of the study were to determine the prevalence of symptoms of OSAS and the differences in dentofacial features of army personnel based in Kelantan who are at high risk and low risk of having OSAS, and to fmd factors associated with the risk of having OSAS. 911 army personnel based in the Des a Pahlawan camp were randomly selected to answer the Malay version of Berlin questionnaire. The distributions of symptoms of OSAS were determined and subjects were categorised as being either at high risk or low risk of having OSAS. Dental study models, lateral cephalometric radiographs and neck circumference for the determination of the dentofacial dimensions were taken from 35 high risk and 37 low risk subjects. A proportion of these subjects underwent overnight sleep studies. Results: 661 questionnaires were returned. The mean age of total participants was 31.4 years (standard deviation (SD) 6.45) while the mean BMI was 24.4 kg I m2 (SD 2.47). There was a range of prevalence of the main symptoms of OSAS with 45 subjects (6.8%, 95o/o CI: 5.0-9.0) categorised in the high risk group for OSAS. There were no significant differences in age and BW between the 35 high risk and 37 low risk subjects that formed the subsequent comparison groups. The neck circumference, PNS_P (length of the soft palate), MPT (maximum soft palate thickness), MPH (distance between the mandibular plane and the hyoid bone), maxillary intermolar distance, mandibular intermolar distance and middle PAS (posterior airway space) were significantly different between both groups. There were significant associations between the following variables and the risk of having OSAS: mandibular intermolar distancePNS_P and MPH. The current study demonstrates presence of symptoms ofOSAS and the distinct dentofacial features in subjects at high risk of OSAS. This study also confmns that symptoms of OSAS still exist even without the classical sign of OSAS, i.e. obesity. It also shows that greater attention should be paid to the evaluation of the dentofacial features in subjects with a low BMI at high risk for the disorder.